Comparative Analysis of The Performance of CCTV Camera Transmission Media Using UTP Cable and Optical Fiber - Suharto, Shelly Adiristy Feby; Novianti, Atik; Atmadja, Martono Dwi; Darmono, Hendro (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
CCTV is an important part of maintaining security in the State Polytechnic of Malang, especially the Telecommunications Lab. In the installation of CCTV, the transmission media plays an important role. In this context, UTP cable and optical fiber are commonly used. The purpose of this research is to compare CCTV camera transmission using UTP cable and optical fiber using quantitative research methods with 3 kinds of tests. QoS parameter testing with TIPHON version standardization, network speed testing, and video quality testing using SSIM and PSNR parameters. Optical fiber delay testing gets an average value of 4.28976 ms and UTP cable of 4.44135 ms. The average jitter of optical fiber is 0.0017 ms and UTP cable is 0.2066 ms. In addition, the packet loss value shows that optical fiber has an average percentage of 8% while UTP cable is 11%. Speed testing shows that optical fiber has an upload speed of 987.52 Mbps and a download of 990.34 Mbps, UTP cable shows an upload of 978.98 Mbps and a download of 978.8 Mbps. While video quality testing shows UTP average PSNR value 30.480694 dB and SSIM 0.9158403 dB, and optical fiber with PSNR value 28.443975 dB, SSIM 0.8897703 dB.